Equity in protection: bridging global data gaps for an EBV vaccine—a systematic review and meta-analysis - Helen R Stagg; Ting Shi; Simran Kapoor; Marisa D Muckian; Vesa Qarkaxhija; Tomos Morgan (BMJ Global Health)
Introduction Epstein–Barr virus (EBV) is linked to multiple malignancies and autoimmune conditions, with different disease burdens globally. Pharmaceutical companies and researchers are placing substantial investment in the development of EBV vaccines. To ensure optimal vaccine roll-out, particularly in resource-limited settings, it is essential to have data on the age at acquisition of EBV. This study aimed to systematically review and meta-analyse seroprevalence by age and country, WHO region and country income level, identify knowledge gaps, and determine an approach to bridge these gaps.Methods MEDLINE, Embase and Web of Science were searched on 22 March 2022 for studies that measured EBV seroprevalence by age. An updated search was conducted on 22 October 2022. There were no language restrictions. Papers were assessed for quality using an adapted version of the Downs and Black checklist. Seroprevalence by age was estimated using a fixed-effect (country) or random-effects (WHO region and income) meta-analysis. This review has been registered on PROSPERO (CRD42022349900).Results Only one country (USA) had enough data for a country meta-analysis. WHO regional analyses revealed the Western Pacific region to have a higher seroprevalence in younger age groups than other WHO regions. Country income level better explained seroprevalence trends per age. Middle-income countries displayed a quicker rise to balance seroprevalence than high-income countries, with a 30% absolute increase in 0- to 4-year-olds in middle-income than in high-income countries (59% [95% CI 28 to 91%, I2=99%] vs 29% [95% CI 16 to 41%, I2=99%]).Conclusion This first meta-analysis producing estimates of EBV seroprevalence by age provides crucial information to guide governments when using a vaccine for EBV. However, data variability and limited consistency of methodologies and EBV seroprevalence measurements hindered comprehensive meta-analyses across all WHO regions and countries. This study provides an interim framework for the extrapolation of seroprevalence using country-specific income levels to aid vaccine roll-out decisions.PROSPERO registration number CRD42022349900